DEVELOPMENT OF BASIC COMPETENCY ASSESSMENT INSTRUMENTS ASSESSING STUDENTS IN ISLAMIC CULTURAL HISTORY (SKI) IN MIN 1 PASURUAN - Muhammad Abdullah (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2021)
Efforts to create effectiveness in learning continue to be carried out in the form of widespread innovations in the emerging education sector, this is done in order to create maximum knowledge transfer to students. Because learning in students is dominated by communication elements that read, listen and write, another competency that also affects the learning process is listening competence. So it needs to be considered in developing competencies that must be mastered by these students. To maximize student competence in the listening aspect, suitable tools are needed. This article describes the development of the basic competency assessment instrument for listening to the SKI subjects at MIN 1 Pasuruan. The research method used is to use research & development in the ADDIE version. The results of the study concluded that 1. The assessment instrument can be used as a reference for teachers in collecting information and data to provide students with basic competence in listening. 2. Listening skills assessment techniques for MIN 1 Pasuruan, including: performance, portfolio and gifts. As for the assessment of the basic development assessment instrument listening to students on the SKI subject at MIN 1 Pasuruan, including the stages including: (1) analysis (analysis), (2) design (design), (4) development (Develop), (5) implementation ( Implement), and (6) evaluation (Evaluate)